Carbon nanotube-porous copper composite current collector and preparation method thereof and silicon negative electrode

By using carbon nanotube-porous copper composite fluid collector and chemical vapor deposition technology in silicon negative electrode materials, the problems of poor interface stability and low conductivity caused by volume expansion during charging and discharging of lithium-ion batteries are solved, and efficient battery circulation performance and electrical conductivity are achieved.

CN119753779APending Publication Date: 2025-04-04JIANGXI ZHIKE NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411750412.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The silicon negative electrode material is caused by disordered volume expansion during charging and discharging of lithium-ion batteries, and the SEI layer is repeatedly broken and generated. Combined with the problem of poor conductivity, the application of silicon negative electrode is seriously restricted.

Method used

The carbon nanotube-porous copper composite current collector is used as the current collector of the silicon negative electrode material, and a micro-nano porous structure is formed by chemical etching, and a porous copper/carbon nanotube composite plating layer with a honeycomb dendrite structure is formed by electrodeposition. The silicon layer is deposited in combination with chemical vapor deposition technology to improve the interface stability and conductivity of the silicon negative electrode material.

Benefits of technology

It effectively alleviates the volume expansion of silicon material during charging and discharging, enhances the binding force between silicon particles and current collector, improves the cycling performance and conductivity of the battery, and realizes a lithium-ion battery with high capacity and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164855400000141
    Figure BDA0005164855400000141
Patent Text Reader

Abstract

The present invention provides a carbon nanotube-porous copper composite current collector and a preparation method thereof and a silicon negative electrode, which belongs to the field of lithium battery negative electrodes. The composite current collector preparation method includes: using a mixed solution of hydrochloric acid and an aqueous hydrogen peroxide solution as an etching solution, immersion chemical etching of a copper foil, and obtaining a primary current collector; using a porous copper current collector as a cathode, and using a copper salt-carbon nanotube suspension as an electrolyte for electrodeposition, to obtain a carbon nanotube-porous copper composite current collector with a honeycomb dendrite structure. Silicon is then deposited on the composite current collector by chemical vapor deposition to obtain a silicon negative electrode. The porous copper / carbon nanotube current collector-based silicon negative electrode prepared by the present invention is a self-supporting structure, does not require a non-conductive adhesive, and the microscopic porous structure can well alleviate the volume expansion caused by the silicon material during the charge and discharge process, and has a binding effect on the silicon particles, effectively preventing the silicon material from falling off, and significantly improving the coulomb efficiency and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery negative electrodes, and particularly relates to a carbon nanotube-porous copper composite current collector and a preparation method thereof, and a silicon negative electrode. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles, electronic devices, energy storage and other fields due to their high energy density, small size and long cycle life. Graphite, as the most popular negative electrode active material for lithium-ion batteries, has the advantages of low price, long cycle life and good conductivity. However, as people's requirements for battery energy density continue to increase, silicon negative electrodes with high lithium-ion capacity have gradually become a research hotspot.

[0003] Compared with the theoretical capacity of 372mAh / g of graphite, silicon has an extremely high specific capacity of 4200mAh / g, showing good development prospects. However, the silicon material will undergo severe disordered volume expansion during the charging and discharging process, which will cause the electrode material to pulverize and the SEI layer to break and form repeatedly. In addition, problems such as poor conductivity have seriously restricted the application of silicon negative electrodes. On the other hand, the current silicon negative electrode still uses traditional copper foil as the current collector, and uses binders and conductive agents to load powdered silicon negative electrode materials on the surface of the copper foil with a smooth surface. Therefore, the severe disordered volume expansion of the silicon negative electrode material will cause the silicon particles to break, resulting in a decrease in the bonding strength with the current collector, causing the silicon material to fall off during the battery cycle, resulting in problems such as increased battery internal resistance and capacity attenuation.

[0004] At present, the methods to improve silicon negative electrodes are mostly focused on technologies such as silicon material nano-materials and silicon-carbon composites to alleviate the huge volume changes of silicon during charging and discharging and improve the conductivity of the material. However, carbon-coated nano-silicon particles have defects such as complex preparation process and high cost of nano-silicon production; while silicon-carbon composite materials as battery negative electrodes can alleviate problems such as volume expansion and poor conductivity to a certain extent, but they also face problems such as poor stability of the current collector-silicon interface.

[0005] In summary, although the current silicon negative electrode modification technology has alleviated the material volume expansion and conductivity problems to a certain extent, the problem of poor interface stability between the current collector and the silicon negative electrode material caused by the material volume expansion still cannot be effectively solved, causing the silicon material to fall off from the current collector surface during the cycle, and then the battery capacity decays seriously. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a carbon nanotube-porous copper composite current collector and a preparation method thereof and a silicon negative electrode, aiming to solve at least one technical problem in the background technology.

[0007] The present invention is achieved in that:

[0008] The first aspect of the present invention provides a method for preparing a carbon nanotube-porous copper composite current collector, the preparation method comprising the following steps:

[0009] Using copper foil as a current collector substrate and a mixture of hydrochloric acid and hydrogen peroxide solution as an etching solution, the copper foil is subjected to immersion chemical etching to obtain a primary current collector with a micro-nano rough structure on the surface;

[0010] Using the primary current collector as a cathode and a copper salt-carbon nanotube suspension as an electrolyte, electrodeposition is performed to form a composite coating of porous copper and carbon nanotubes on the surface of the primary current collector, thereby obtaining a carbon nanotube-porous copper composite current collector having a honeycomb dendrite structure;

[0011] Wherein, the electrolyte comprises sulfuric acid, modified carbon nanotubes, copper sulfate, additives and deionized water; the modified carbon nanotubes are carbon nanotubes after acidification treatment.

[0012] The present invention forms a micro-nano porous structure on the surface of the copper foil by chemical etching to increase the surface roughness. This rough surface structure helps to enhance the adhesion between the subsequent porous copper / carbon nanotube composite coating and the substrate, and improves the overall stability. The honeycomb porous copper structure can provide an internal space for the subsequent deposition of silicon, and has a binding effect on the active material of the silicon particles to avoid falling off during the charge and discharge process. At the same time, the high aspect ratio of the composite carbon nanotubes in the porous copper also helps to alleviate the volume change of the silicon material during the charge and discharge process and prevent it from falling off. In addition, the copper / carbon nanotube composite material can also form a conductive network to improve the conductivity of the current collector. The carbon nanotubes in the porous structure have a higher affinity for silicon, which can effectively regulate the uniform deposition of silicon on the surface and have a binding effect on silicon.

[0013] Furthermore, the concentration of each component in the electrolyte is: sulfuric acid 10g / L to 100g / L, modified carbon nanotubes 0.5g / L to 2g / L, copper sulfate 2g / L to 20g / L;

[0014] The additive is selected from at least two of 1mg / L to 10mg / L sodium polydisulfide propane sulfonate (SPS), 5mg / L to 20mg / L sodium 3-mercapto-1-propane sulfonate (MPS), 1mg / L to 10mg / L polydimethylamine (PDDA), 0.1g / L to 5g / L polyvinyl pyrrolidone (PVP) and 10mg / L to 100mg / L polyethylene glycol (PEG). Among them, SPS can refine the grains and improve the density of the copper layer. MPS and PDDA can be adsorbed on the surface of carbon nanotubes, change their surface charge and wettability, and promote the deposition of carbon nanotubes on the cathode. PVP and PEG act as dispersants to prevent the clustering of carbon nanotubes and make them evenly distributed in the electrolyte.

[0015] Furthermore, the preparation step of the modified carbon nanotubes includes: mixing nitric acid and sulfuric acid in a volume ratio of 1: (1-5) to obtain a mixed acid solution; adding carbon nanotubes to the mixed acid solution under ultrasound, and treating at a temperature of 40°C to 70°C for 2h to 8h to obtain acidified carbon nanotubes.

[0016] Furthermore, the chemical etching time is 10s to 100s, and the processing temperature is 30°C to 60°C;

[0017] The preparation steps of the etching solution are: mixing hydrogen peroxide with a mass fraction of 30% and deionized water at a volume ratio of 1:(2-10) to obtain a dilute hydrogen peroxide solution; and mixing concentrated hydrochloric acid with a mass fraction of 37% and the dilute hydrogen peroxide solution at a volume ratio of 1:(1-3) to obtain the etching solution.

[0018] Furthermore, in the electrodeposition, the current density is 0.2A / cm 2 ~5A / cm 2 , temperature is 40℃~70℃, time is 5s~30s.

[0019] The second aspect of the present invention provides a carbon nanotube-porous copper composite current collector prepared by the above preparation method.

[0020] The third aspect of the present invention provides a silicon negative electrode, which is obtained by depositing silicon on the carbon nanotube-porous copper composite current collector prepared by the above preparation method to obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0021] The present invention improves the interface stability of the carbon nanotube-porous copper composite current collector-silicon material by chemical vapor deposition of a silicon layer in the porous copper / carbon nanotube, thereby further improving the battery cycle performance.

[0022] Furthermore, the preparation steps of the silicon negative electrode are: loading the carbon nanotube-porous copper composite current collector into a chemical vapor deposition furnace, after evacuating, introducing a mixed gas of silane and nitrogen into the furnace at a preset volume flow rate, heating to 300°C to 600°C, and reacting for 1h to 5h; thereby depositing silicon inside the pores of the carbon nanotube-porous copper composite current collector to obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0023] Furthermore, the vacuum is 0.1Pa to 1Pa, and the preset volume flow rate is 100sccm to 300sccm.

[0024] Furthermore, the volume ratio of the silane to nitrogen mixture is 1:(2-8).

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention uses a carbon nanotube-porous copper composite coating as a current collector for silicon negative electrode materials. The microscopic porous structure inside the current collector can well alleviate the volume expansion caused by the silicon material during the charge and discharge process, and has a binding effect on the silicon particles, effectively preventing them from falling off, which helps to improve the structural stability of the silicon negative electrode material and the cycle performance of the battery; the carbon nanotubes in the carbon nanotube-porous copper composite coating are tightly connected to the current collector and silicon particles through active functional groups, effectively improving the interface bonding strength and conductivity. The silicon nanoparticles obtained by chemical vapor deposition can be fixed inside the carbon nanotube-porous copper composite coating and tightly combined with each other, enhancing the cycle stability of the battery.

[0027] 2. The carbon nanotube-porous copper composite current collector-based silicon negative electrode prepared by the present invention is a self-supporting porous structure, which does not require a non-conductive adhesive, and is helpful to improve conductivity and increase rate performance; at the same time, it can prevent the shedding of finer silicon particles produced by the expansion and crushing of silicon particles.

[0028] 3. The half-cell assembled with the carbon nanotube-porous copper composite current collector-based silicon negative electrode of the present invention has an initial reversible capacity of up to 2300 mAh / g, and the capacity retention rate is still 85% after 100 cycles at 0.5C, and the minimum coulombic efficiency of each cycle is as high as over 99%. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] A method for preparing a carbon nanotube-porous copper composite current collector, the method comprising the following steps:

[0031] S1. Using copper foil as a current collector substrate and a mixture of hydrochloric acid and hydrogen peroxide solution as an etching solution, the copper foil is subjected to immersion chemical etching to obtain a primary current collector having a micro-nano rough structure on the surface;

[0032] In a specific implementation, the etching solution is a mixture of 37% by mass concentrated hydrochloric acid and a dilute hydrogen peroxide solution in a volume ratio of 1:(1-3), and the dilute hydrogen peroxide solution is a mixture of 30% by mass hydrogen peroxide and deionized water in a volume ratio of 1:(2-10); concentrated hydrochloric acid is the main reagent for acid etching, copper is oxidized to +1 valence cuprous by concentrated hydrochloric acid and combined with chloride ions to form a difficultly dissociated complex ion, and the role of hydrogen peroxide is to enhance the oxidizability of concentrated hydrochloric acid;

[0033] In a specific implementation, the temperature during chemical etching is 30°C to 60°C, for example, 60°C, 50°C, 40°C, or 30°C; the time for chemical etching is 10s to 100s, for example, 10s, 30s, 40s, 60s, or 100s; but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] S2, using the primary current collector as a cathode and a copper salt-carbon nanotube suspension as an electrolyte to perform electrodeposition, so that a composite coating of copper and carbon nanotubes is formed on the surface of the primary current collector, thereby obtaining a carbon nanotube-porous copper composite current collector having a honeycomb dendrite structure;

[0035] In a specific implementation, the current density is 0.2A / cm 2 ~5A / cm 2 , the temperature is 40℃~70℃, the time is 5s~30s; the anode in the electrodeposition can be any anode material allowed in the technical field, such as platinum sheet, pure copper, etc.;

[0036] In a specific implementation, the electrolyte includes 10g / L~100g / L sulfuric acid, 0.5g / L~2g / L modified carbon nanotubes, 2g / L~20g / L copper sulfate, additives and deionized water; the additives are selected from at least two of 1mg / L~10mg / L sodium polydisulfide dipropane sulfonate (SPS), 5mg / L~20mg / L sodium 3-mercapto-1-propane sulfonate (MPS), 1mg / L~10mg / L polydimethylamine (PDDA), 0.1g / L~5g / L polyvinyl pyrrolidone (PVP) and 10mg / L~100mg / L polyethylene glycol (PEG).

[0037] In a specific implementation, the modified carbon nanotubes are carbon nanotubes after acid treatment, and the preparation steps include: mixing nitric acid and sulfuric acid in a volume ratio of 1: (1 to 5) to obtain a mixed acid solution; adding carbon nanotubes to the mixed acid solution under ultrasound, and treating at a temperature of 40°C to 70°C for 2h to 8h to obtain acidified carbon nanotubes.

[0038] The method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises the above steps S1 and S2 and the following step S3.

[0039] S3. Load the carbon nanotube-porous copper composite current collector into a chemical vapor deposition furnace, evacuate to 0.1Pa~1Pa, and then introduce a mixed gas of silane and nitrogen (volume ratio = 1:2~8) into the furnace at a volume flow rate of 100sccm~300sccm, and react after heating; thereby silicon is deposited inside the pores of the carbon nanotube-porous copper composite current collector to obtain a silicon negative electrode.

[0040] The temperature during chemical vapor deposition is 300°C to 600°C, for example, 450°C. 、 500°C, 600°C, the reaction time is 1h to 5h, for example, 1h, 2h, 3h; but not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0041] Example 1

[0042] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0043] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:5 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 30 seconds at a treatment temperature of 60°C to obtain a primary current collector;

[0044] S2, use sulfuric acid concentration 100g / L, modified carbon nanotube concentration 2g / L, copper sulfate concentration 20g / L, SPS concentration 5mg / L, MPS concentration 10mg / L, PDDA concentration 2mg / L, PVP concentration 0.5g / L and PEG concentration 15mg / L to prepare electrolyte; use platinum sheet as anode and primary current collector as cathode, at a current density of 5A / cm 2 and 50°C for 5s to obtain a carbon nanotube-porous copper composite current collector;

[0045] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.1 Pa, introduce a mixed gas of silane and nitrogen at a flow rate of 200 sccm into the furnace in a mixing ratio of 1:3, heat it to 500°C and react for 2 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0046] Example 2

[0047] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0048] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:2 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:1 to obtain a hydrochloric acid-hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid-hydrogen peroxide etching solution for 10 seconds at a treatment temperature of 40°C to obtain a primary current collector.

[0049] S2, use sulfuric acid concentration of 10g / L, modified carbon nanotube concentration of 0.5g / L, copper sulfate concentration of 5g / L, SPS concentration of 1mg / L, MPS concentration of 15mg / L, PDDA concentration of 5mg / L to prepare copper / carbon nanotube electrolyte; use pure copper as anode and primary current collector as cathode, and conduct the electrolysis at a current density of 2A / cm 2 and 40°C, and then the carbon nanotube-porous copper composite current collector was obtained after electrodeposition for 20s;

[0050] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.2 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 150 sccm, with a mixing ratio of 1:4, and add it to 500°C for reaction for 3 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0051] Example 3

[0052] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0053] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:10 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 100 seconds at a treatment temperature of 60°C to obtain a primary current collector.

[0054] S2, use sulfuric acid concentration 50g / L, modified carbon nanotube concentration 1g / L, copper sulfate concentration 10g / L, SPS concentration 10mg / L, PVP concentration 5g / L to prepare copper / carbon nanotube electrolyte; use pure copper as anode and primary current collector as cathode at a current density of 1A / cm 2 and 50°C for 30s to obtain a carbon nanotube-porous copper composite current collector;

[0055] S2. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.5 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 100 sccm, with a mixing ratio of 1:2, heat it to 500°C and react for 2 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0056] Example 4

[0057] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0058] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:8 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with a dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid-hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid-hydrogen peroxide etching solution for 60 seconds at a treatment temperature of 50°C to obtain a primary current collector.

[0059] S2, using sulfuric acid concentration of 60g / L, modified carbon nanotube concentration of 1.5g / L, copper sulfate concentration of 15g / L, SPS concentration of 8mg / L, PDDA concentration of 6mg / L and PEG concentration of 80mg / L to prepare copper / carbon nanotube electrolyte; using platinum sheet as anode and primary current collector as cathode, at a current density of 3A / cm 2 and 50°C for 20s to obtain a carbon nanotube-porous copper composite current collector.

[0060] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.3 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 300 sccm, with a mixing ratio of 1:4, and heat it to 600°C for 1 hour to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0061] Example 5

[0062] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0063] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:3 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:2 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 40 seconds at a treatment temperature of 30°C to obtain a primary current collector.

[0064] S2, using sulfuric acid concentration 40mL / L, modified carbon nanotube concentration 0.8g / L, copper sulfate concentration 8g / L, SPS concentration 6mg / L, MPS concentration 15mg / L, PVP concentration 3g / L and PEG concentration 60mg / L to prepare copper / carbon nanotube electrolyte;

[0065] The platinum sheet was used as the anode and the primary current collector was used as the cathode. 2 The carbon nanotube-porous copper composite current collector was obtained after electrodeposition at 50°C for 10s.

[0066] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.3 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 200 sccm, with a mixing ratio of 1:3, and add it to 450°C for reaction for 3 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0067] Comparative Example 1

[0068] A method for preparing a carbon nanotube-copper composite current collector-based silicon negative electrode comprises:

[0069] S1. Select 6-micron thick copper foil as the reaction substrate. Prepare the electrolyte with sulfuric acid concentration of 100 g / L, modified carbon nanotube concentration of 2 g / L, copper sulfate concentration of 20 g / L, SPS concentration of 5 mg / L, MPS concentration of 10 mg / L, PDDA concentration of 2 mg / L, PVP concentration of 0.5 g / L and PEG concentration of 15 mg / L; use platinum sheet as anode and copper foil as cathode, and conduct the reaction at a current density of 5 A / cm 2 and 50°C for 5s to obtain a carbon nanotube-copper composite current collector;

[0070] S2. Place the carbon nanotube-copper composite current collector into the tray of a chemical vapor deposition furnace, evacuate the furnace to 0.1 Pa, introduce a mixed gas of silane and nitrogen at a flow rate of 200 sccm into the furnace in a mixing ratio of 1:3, heat it to 500°C and react for 2 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0071] Compared with Example 1, since the copper foil in this comparative example is not chemically etched, the surface roughness of the copper foil is relatively low, the copper / carbon nanotube composite coating is not firmly bonded to the substrate, and the battery cycle performance is relatively poor.

[0072] Comparative Example 2

[0073] A method for preparing a porous copper current collector-based silicon negative electrode comprises:

[0074] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:2 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:1 to obtain a hydrochloric acid-hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid-hydrogen peroxide etching solution for 10 seconds at a treatment temperature of 40°C to obtain a primary current collector;

[0075] S2. Place the primary current collector in the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.2 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 150 sccm, with a mixing ratio of 1:4, and heat it to 500°C for 3 hours to finally obtain a porous copper current collector silicon negative electrode.

[0076] Compared with Example 2, this comparative example does not have a copper / carbon nanotube composite electrodeposition process, resulting in no obvious porous structure formed on the current collector surface, and limited ability to alleviate the volume expansion of the silicon material, resulting in the silicon material falling off from the current collector surface during the battery cycle process and the battery capacity decay.

[0077] Comparative Example 3

[0078] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0079] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:10 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 100 seconds at a treatment temperature of 60°C to obtain a primary current collector;

[0080] S2, use sulfuric acid concentration 50g / L, modified carbon nanotube concentration 0.3g / L, copper sulfate concentration 10g / L, SPS concentration 10mg / L, PVP concentration 5g / L to prepare copper / carbon nanotube electrolyte; use pure copper as anode and primary current collector as cathode at a current density of 1A / cm 2 and 50°C for 30s to obtain a carbon nanotube-porous copper composite current collector.

[0081] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.5 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 100 sccm, with a mixing ratio of 1:2, heat it to 500°C and react for 2 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0082] Compared with Example 3, this comparative example cannot effectively regulate the silicon active material because the concentration of modified carbon nanotubes in the composite electrolyte is low and the carbon nanotube content in the electrodeposited porous copper / carbon nanotube structure is too small, resulting in uneven deposition of silicon materials and agglomeration of silicon particles on the surface of the current collector, which leads to poor battery cycle performance and reduced coulombic efficiency.

[0083] Comparative Example 4

[0084] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0085] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:8 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 60 seconds at a treatment temperature of 50°C to obtain a primary current collector;

[0086] S2, use sulfuric acid concentration 60g / L, modified carbon nanotube concentration 1.5g / L, copper sulfate concentration 15g / L, SPS concentration 8mg / L to prepare copper / carbon nanotube electrolyte; use platinum sheet as anode and primary current collector as cathode, at a current density of 3A / cm 2 and 50°C for 20s to obtain a carbon nanotube-porous copper composite current collector;

[0087] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.3 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 300 sccm, with a mixing ratio of 1:4, and heat it to 600°C for 1 hour to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0088] Compared with Example 4, this comparative example only uses one additive, resulting in a smaller pore structure and carbon nanotube loading during electrodeposition of porous copper / carbon nanotubes, resulting in uneven silicon deposition and limited ability to restrain silicon from expanding and falling off, thereby reducing the battery capacity and cycle performance.

[0089] Comparative Example 5

[0090] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0091] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:3 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:2 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 140 seconds at a treatment temperature of 30°C to obtain a primary current collector;

[0092] S2, use sulfuric acid concentration 40mL / L, modified carbon nanotube concentration 0.8g / L, copper sulfate concentration 8g / L, SPS concentration 6mg / L, MPS concentration 15mg / L, PVP concentration 3g / L and PEG concentration 60mg / L to prepare copper / carbon nanotube electrolyte; use platinum sheet as anode and primary current collector as cathode, and conduct the electrolysis at a current density of 3A / cm 2 The carbon nanotube-porous copper composite current collector was obtained after electrodeposition at 50°C for 10s;

[0093] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.3 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 200 sccm, with a mixing ratio of 1:3, and add it to 450°C for reaction for 3 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0094] Compared with Example 5, the copper foil surface in this comparative example is severely oxidized due to the long chemical etching time, resulting in pits visible to the naked eye, and a copper oxide layer is produced on the surface, which reduces its bonding strength with the electrodeposited porous copper / carbon nanotubes and increases the interface resistance between the current collector and the silicon material, thereby reducing the battery cycle performance.

[0095] Comparative Example 6

[0096] A method for preparing a carbon nanotube-porous copper composite current collector-based silicon negative electrode comprises:

[0097] S1. Select a 6-micron thick copper foil as a reaction substrate, mix 30% by mass hydrogen peroxide with deionized water in a volume ratio of 1:10 to obtain a dilute hydrogen peroxide solution; mix 37% by mass concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:3 to obtain a hydrochloric acid hydrogen peroxide etching solution; immerse the cleaned copper foil in the hydrochloric acid hydrogen peroxide etching solution for 100 seconds at a treatment temperature of 60°C to obtain a primary current collector;

[0098] S2, use sulfuric acid concentration of 50g / L, modified carbon nanotube concentration of 2.5g / L, copper sulfate concentration of 10g / L, SPS concentration of 10mg / L, PVP concentration of 5g / L to prepare copper / carbon nanotube electrolyte; use pure copper as anode and primary current collector as cathode at a current density of 1A / cm 2 and 50°C for 30s to obtain a carbon nanotube-porous copper composite current collector.

[0099] S3. Place the carbon nanotube-porous copper composite current collector into the tray of the chemical vapor deposition furnace, evacuate the furnace to 0.5 Pa, introduce a mixed gas of silane and nitrogen into the furnace at a flow rate of 100 sccm, with a mixing ratio of 1:2, heat it to 500°C and react for 2 hours to finally obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

[0100] Compared with Example 3, in this comparative example, because the concentration of modified carbon nanotubes in the composite electrolyte is high, carbon nanotubes agglomerate, resulting in a loose structure of the electrodeposited porous copper / carbon nanotubes, reduced strength, and increased resistance of the current collector itself. In addition, after the first cycle of the battery, the expansion of silicon causes the honeycomb structure of the current collector to pulverize, resulting in a decrease in battery cycle performance and coulombic efficiency.

[0101] The silicon negative electrodes prepared by Examples 1 to 5 and Comparative Examples 1 to 6 were used in half-cells, respectively, and button cells were made and then electrochemical tests were performed. The electrolyte used in the test was 1 mol / L lithium hexafluorophosphate dissolved in ethylene carbonate: diethyl carbonate in a mass ratio of 1:1, the diaphragm was PP, and the lithium sheet was used as the counter electrode. The battery cycle test was performed at room temperature. First, the assembled button cell was activated, and the battery was cycled 3 times at a current density of 0.1C, and then the battery was cycled 100 times to evaluate the coulombic efficiency and cycle performance. During the test, the battery was first discharged, and lithium ions reacted with the silicon material to form a lithiation reaction; the battery was charged, and the lithium ions were removed from the silicon material and redeposited on the lithium sheet to complete a cycle.

[0102] Table 1

[0103]

[0104] It can be seen from Table 1 that the carbon nanotube-porous copper composite current collector-based silicon negative electrode prepared in the embodiment of the present invention has good coulombic efficiency and cycle performance. This is mainly because the porous copper / carbon nanotube structure can well alleviate the volume expansion of the silicon material caused by lithiation, and improve the bonding force between the silicon material and the current collector interface, effectively avoid the silicon material from falling off, and improve the conductivity.

[0105] The above description is only used as a preferred embodiment of the present invention, and is intended to illustrate but not limit the scope of the present invention. Under the premise of following the basic principles of the present invention, any form of modification, alternative or further optimization and improvement shall be deemed to be within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a carbon nanotube-porous copper composite current collector, characterized in that: The preparation method comprises the following steps: Using copper foil as a current collector substrate and a mixture of hydrochloric acid and hydrogen peroxide solution as an etching solution, the copper foil is subjected to immersion chemical etching to obtain a primary current collector with a micro-nano rough structure on the surface; Using the primary current collector as a cathode and a copper salt-carbon nanotube suspension as an electrolyte, electrodeposition is performed to form a composite coating of porous copper and carbon nanotubes on the surface of the primary current collector, thereby obtaining a carbon nanotube-porous copper composite current collector having a honeycomb dendrite structure; Wherein, the electrolyte comprises sulfuric acid, modified carbon nanotubes, copper sulfate, additives and deionized water; the modified carbon nanotubes are carbon nanotubes after acidification treatment.

2. The method for preparing the carbon nanotube-porous copper composite current collector according to claim 1, characterized in that: The concentrations of the components in the electrolyte are: 10 g / L to 100 g / L sulfuric acid, 0.5 g / L to 2 g / L modified carbon nanotubes, and 2 g / L to 20 g / L copper sulfate; The additive is selected from at least two of 1 mg / L to 10 mg / L sodium polydisulfide dipropane sulfonate, 5 mg / L to 20 mg / L sodium 3-mercapto-1-propane sulfonate, 1 mg / L to 10 mg / L polydimethylamine, 0.1 g / L to 5 g / L polyvinyl pyrrolidone and 10 mg / L to 100 mg / L polyethylene glycol.

3. The method for preparing the carbon nanotube-porous copper composite current collector according to claim 1 or 2, characterized in that: The preparation steps of the modified carbon nanotubes include: mixing nitric acid and sulfuric acid in a volume ratio of 1: (1-5) to obtain a mixed acid solution; adding carbon nanotubes to the mixed acid solution under ultrasound, treating at a temperature of 40° C. to 70° C. for 2h to 8h to obtain acidified carbon nanotubes.

4. The method for preparing the carbon nanotube-porous copper composite current collector according to claim 1, characterized in that: The chemical etching time is 10s to 100s, and the processing temperature is 30°C to 60°C; The preparation steps of the etching solution are: mixing 30% hydrogen peroxide with deionized water in a volume ratio of 1:(2-10) to obtain a dilute hydrogen peroxide solution; and mixing 37% concentrated hydrochloric acid with the dilute hydrogen peroxide solution in a volume ratio of 1:(1-3) to obtain the etching solution.

5. The method for preparing the carbon nanotube-porous copper composite current collector according to claim 1, characterized in that: During the electrodeposition, the current density was 0.2 A / cm 2 ~5A / cm 2 , temperature is 40℃~70℃, time is 5s~30s.

6. The carbon nanotube-porous copper composite current collector prepared by the preparation method according to any one of claims 1 to 5.

7. A silicon negative electrode, characterized in that: Silicon is deposited on the carbon nanotube-porous copper composite current collector prepared by the preparation method according to any one of claims 1 to 5 to obtain a carbon nanotube-porous copper composite current collector-based silicon negative electrode.

8. The silicon negative electrode according to claim 7, characterized in that: The preparation steps of the silicon negative electrode are as follows: loading a carbon nanotube-porous copper composite current collector into a chemical vapor deposition furnace, evacuating the furnace, introducing a mixed gas of silane and nitrogen into the furnace at a preset volume flow rate, heating to 300°C to 600°C, and reacting for 1h to 5h; thereby depositing silicon inside the pores of the carbon nanotube-porous copper composite current collector to obtain the carbon nanotube-porous copper composite current collector-based silicon negative electrode.

9. The silicon negative electrode according to claim 8, characterized in that: The vacuum is 0.1Pa to 1Pa, and the preset volume flow rate is 100sccm to 300sccm.

10. The silicon negative electrode according to claim 8, characterized in that: The volume ratio of the silane to nitrogen mixture is 1:(2-8).

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121097178A